“Partners Limited”, the changing facet of private legal practices entity in Malaysia and Singapore - Abd Rahman, Hussin Mohamed; Alias, Siti Aliza; Abd Ghadas, Zuhairah Ariff (2016)
Prior to 2012, advocates and solicitors in Malaysia are only allowed to carry out their private practices via sole proprietorships or partnerships structure. With the passing of the Legal Profession (Amendment) Act 2012 in July 2012, foreign law firms are allowed to operate in Malaysian. Such development indicated that there should be changes to the business vehicles for private legal practices in Malaysia. In Singapore, the legal professions enjoy more business options compared to their counterparts in Malaysia. The advocates and solicitors in Singapore can choose to carry out their private practices in the form of sole proprietorships, partnerships, Law Corporation, limited partnerships and limited liability partnerships. The Singapore LLP is in fact the first LLP being introduced in the Southeast Asia region. Other than the LLPs, another interesting development in the Singapore legal fraternity is the law corporation. The business vehicle enables lawyers in Singapore to carry out their private practices in form of a company.